Long‐chain acyl‐CoA synthetase 6 regulates lipid synthesis and mitochondrial oxidative capacity in human and rat skeletal muscle. (8th November 2016) - Teodoro, Bruno G.; Sampaio, Igor H.; Bomfim, Lucas H. M.; Queiroz, André L.; Silveira, Leonardo R.; Souza, Anderson O.; Fernandes, Anna M. A. P.; Eberlin, Marcos N.; Huang, Tai‐Yu; Zheng, Donghai; Neufer, P. Darrell; Cortright, Ronald N.; et al.
Abstract : Key points: Long‐chain acyl‐CoA synthetase 6 (ACSL6) mRNA is present in human and rat skeletal muscle, and is modulated by nutritional status: exercise and fasting decrease ACSL6 mRNA, whereas acute lipid ingestion increase its expression. ACSL6 genic inhibition in rat primary myotubes decreased lipid accumulation, as well as activated the higher mitochondrial oxidative capacity programme and fatty acid oxidation through the AMPK/PGC1‐α pathway. ACSL6 overexpression in human primary myotubes increased phospholipid species and decreased oxidative metabolism. Abstract: Long‐chain acyl‐CoA synthetases (ACSL 1 to 6) are key enzymes regulating the partitioning of acyl‐CoA species toward different metabolic fates such as lipid synthesis or β‐oxidation. Despite our understanding of ecotopic lipid accumulation in skeletal muscle being associated with metabolic diseases such as obesity and type II diabetes, the role of specific ACSL isoforms in lipid synthesis remains unclear. In the present study, we describe for the first time the presence of ACSL6 mRNA in human skeletal muscle and the role that ACSL6 plays in lipid synthesis in both rodent and human skeletal muscle. ACSL6 mRNA was observed to be up‐regulated by acute high‐fat meal ingestion in both rodents and humans. In rats, we also demonstrated that fasting and chronic aerobic training negatively modulated the ACSL6 mRNA and other genes of lipid synthesis. Similar results were obtained following ACSL6 knockdown in rat myotubes, which was associated with a decreased accumulation of TAGs and lipid droplets. Under the same knockdown condition, we further demonstrate an increase in fatty acid content, p‐AMPK, mitochondrial content, mitochondrial respiratory rates and palmitate oxidation. These results were associated with increased PGC‐1α, UCP2 and UCP3 mRNA and decreased reactive oxygen species production. In human myotubes, ACSL6 overexpression reduced palmitate oxidation and PGC‐1α mRNA. In conclusion, ACSL6 drives acyl‐CoA toward lipid synthesis and its downregulation improves mitochondrial biogenesis, respiratory capacity and lipid oxidation. These outcomes are associated with the activation of the AMPK/PGC1‐α pathway. Key points: Long‐chain acyl‐CoA synthetase 6 (ACSL6) mRNA is present in human and rat skeletal muscle, and is modulated by nutritional status: exercise and fasting decrease ACSL6 mRNA, whereas acute lipid ingestion increase its expression. ACSL6 genic inhibition in rat primary myotubes decreased lipid accumulation, as well as activated the higher mitochondrial oxidative capacity programme and fatty acid oxidation through the AMPK/PGC1‐α pathway. ACSL6 overexpression in human primary myotubes increased phospholipid species and decreased oxidative metabolism.